Classifying the Involvement of Men and Women in Climate Smart Agricultural Practices in Kayonza Sub-county, Kanungu District, Uganda - Turyasingura, Benson; Ayiga, Natal (International Journal of Energy and Environmental Science, 2022)
Globally, climate change is currently recognized as one of the most serious risks to communities' socio-economic activity, health, and livelihood. Climate Smart Agriculture is an essential tactic to developing the technical, policy, and investment conditions that enable actions aimed at achieving sustainable agricultural development for food and nutrition security in a changing climate. The purpose of this study was therefore classifying the involvement of men and women in climate smart agricultural practices in Kayonza sub-county, Kanungu district, Uganda. The study was guided by the specific objectives which include investigating the engagement of both men and women in climate-smart practices, establishing different climate-smart practices that are being used and assessing the climate smart agricultural practices adopted in in Kayonza sub-county. The study used descriptive research design utilizing both qualitative and quantitative data collection and analyses methods. Using simple random and purposive sampling techniques, a total of 374 respondents were selected to participate in the study. Questionnaires, key informant interviews, observation methods of data collection were used in this study. It was found out that both men and women were involved in the planting of trees and crops on farms that are typically used for fruit, fodder. Improved cooking stoves, fisheries and aquaculture, pasture management and planting of plant tolerant verities were among the CSA practices. The study recommends that the government should develop a strategy plan for gender quality based on goals that reflect an awareness of the economic and social implications of compromised climate smart agriculture. It was also concluded that both men and women were active in climate-smart farming methods.
Keywords: Involvement of Men and Women; Climate Smart Agriculture; Kayonza Sub-county